Catalogue of Egyptian funerary papyri in Danish collections - Christiansen, Thomas, (CNI Publications ;)
The present volume contains a publication of all known Egyptian funerary manuscripts in Danish colorlections.While the majority of texts are written on papyrus, the catalogue also includes several pieces of mummy linen.Only such material as is considered likely to have formed parts of actual burials are included; hence the volume does not include any of the Osirian ritual texts in the Papyrus Carlsberg Collection which all derive from a temple context.The purpose of the catalogue is to provide material for the study of Egyptian funerary texts.Thus, rather than focusing on the better-preserved and more impressive items, an exhaustive catalogue, representing a broader range of traditions is presented here.Five colorlections, all located in Copenhagen, are represented by the twenty-two manuscripts here published: the Papyrus Carlsberg Collection and the Papyrus Hauniensis Collection (University of Copenhagen), Ny Carlsberg Glyptotek, the National Museum, and Thorsvaldsens Museum.